'Making financial sense of the future': actuaries and the management of climate-related financial risk. Issue 1 (2nd January 2023) - Taylor, Nick
ABSTRACT: This paper seeks to explore how professionals in the financial sector understand the challenge that climate change presents to economy and society. It is a case study into how 'climate-related financial risk' is understood in a particular area of expertise – within the actuarial profession. There is an increasingly prominent claim among financial regulators that climate change should be considered as an issue of financial risk and stability; it is argued that this will drive capital towards green ends, and an orderly low carbon transition. Responding to this, actuaries are seeking to establish climate-related risk as part of their professional jurisdiction. Yet they are struggling to do so because of their relationship to the investment chain and because the tools they employ for risk management, mostly drawn from financial economics, are fundamentally failing to consider, quantify and financialise climate risks. Instead, the profession is moving toward scenario-based tools for managing climate-related uncertainty that incorporate narratives about policy interventions and market reaction. The paper draws on interviews and ethnographic research conducted with members of the UK-based Institute and Faculty of Actuaries (IFoA) to explore these established and emerging risk management tools and perspectives.